THE ANTIPLASMODIAL AGENTS OF THE STEM BARK OF ENTANDROPHRAGMA ANGOLENSE (MELIACEAE) - Bickii, Jean; Tchouya, Guy Raymond Feuya; Tchouankeu, Jean Claude; Tsamo, Etienne (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
In the search of active principles from the stem bark of Entandrophragma angolense, we submitted the compounds isolated from the dichloromethane – methanol (1:1) extract of the stem bark to antimalarial test against chloroquine resistant strain W2 of Plasmodium falciparum malaria parasite. Only 7-obacunyl acetate and a cycloartane derivative exhibited a good activity, with IC50s of 2 and 5.4 µg/ml respectively. Other compounds were moderately active.